Yield of testing and treatment for tuberculosis among foreign-born persons during contact investigations in the United States: A semi-systematic review. - Andrea Parriott; Mohsen Malekinejad; Amanda P Miller; Hacsi Horvath; Suzanne M Marks; James G Kahn (PLoS ONE)
Background Contact investigation is an important strategy for maintaining control of tuberculosis (TB) in the United States. However, testing and treatment outcomes specifically to foreign-born populations are poorly understood. We reviewed literature on testing and LTBI identified during contact investigations in foreign-born populations living in the US. Methods We conducted a comprehensive search of peer-reviewed and grey literature using Cochrane systematic review methods. We included studies with adult and adolescent populations that were at least 50% foreign-born. Pooled proportions and 95% confidence intervals (CIs) were calculated via inverse-variance weighted meta-analysis, and cumulative proportions were calculated as products of adjacent step proportions. Results We identified 22 studies published between 1997 and 2014 that included at least 50% foreign-born participants. From studies of predominantly (>90%) foreign-born populations, almost all identified contacts were recruited and had valid test results, and 54.8% (95% CI 45.1-62.5%) of contacts with valid test results tested positive. From studies of majority (50% to 90%) foreign-born populations, 78.4% (95% CI 78.0-78.9%) of identified contacts were recruited, 92.0% (95% CI 91.6-92.3%) of recruited contacts had valid test results, and 38.5% (95% CI 31.9%-44.2%) of persons with valid results tested positive. These proportions varied by test type in studies of predominantly foreign-born populations. For every 1000 contacts identified in predominantly foreign-born populations, we estimate that 535 (95% CI 438 to 625) will test positive, and 354 (95% CI 244 to 453) will complete LTBI treatment. For every 1000 contacts identified in majority foreign-born populations, these estimates are 276 (95% CI 230 to 318), and 134 (95% CI 44 to 264), respectively. Conclusions Contact investigation is a high yield activity for identifying and treating foreign-born persons with LTBI, but must be complemented by other tuberculosis control activities in order to achieve continued progress toward TB elimination.